Corporate Characteristics and Corporate Social and Environmental Disclosures Quantity in Nigeria - J. O. Odia (Journal of Accounting, Business and Management (JABM), 2015)
The paper examines the impact of corporate characteristics on corporate social and environmental disclosures in Nigeria. It tests whether there were any association between the quantity of social and environmental disclosure and a number of company characteristics used in previous studies by utilizing the annual reports of 174 listed companies in the Nigerian Stuck Exchange. The disclosures index and content analysis method were adopted for the study to gather data for the CSED quantity measures which include: CSED page, number of sentences, proportion of CSED page to total page of annual reports and disclosure index. Using the OLS regression analysis, the results suggest that there are statistically significant association between five variables (profitability, leverage, reputation, research and development and diversification) and the corporate social and environmental disclosures quantity in Nigeria. Specifically corporate reputation was found to be associated with all the measures of CSED quantity. The outcomes of the study support the legitimacy theory.